Research in personnel and human resources management - Buckley, M. Ronald; Wheeler, Anthony R.; Baur, John E. (Assistant professor); Halbesleben, Jonathon R. B. (Research in personnel and human resources management, 2023)
Volume 41 of Research in Personnel and Human Resources Management offers several original scholarly contributions written by thought leaders in the field of human resources management. These chapters feature the latest research exploring emerging novel areas of HRM. Contributions include an analysis of professional touching behaviour, ideas about the state of our science in HRM, novel integration of work-life flexibility issues, processes that occur in expatriate turnover, suggestions concerning the state of human resource process research, and some comments on the contribution of this series to facilitating research in HRM issues.